118k views
1 vote
What would Nate need to add to his model for it to be equivalent to Joe's model

What would Nate need to add to his model for it to be equivalent to Joe's model-example-1
User Curv
by
4.3k points

1 Answer

5 votes

Joe has the expression:


x+3\cdot1+2(-1)=x+3-2=x+1

And Nate has the expression:


x+4\cdot1=x+4

In order to have the same expression, Nate has to substract 3 units. This can be done by adding 3 "(-1)".

Then Nate would have:


x+4+3(-1)=x+4-3=x+1

Answer: 3 units of "-1" (Option C).

User ThurstonLevi
by
4.5k points